The Impact of Modern Medical Technology on the Transformation of Healthcare Service Contract Structures from Conventional Face-to-Face Contracts to Digital Contracts: An Indonesian Health Law Perspective - Adji Annisa Rahmadina; Prassetyo Edi (Siber Nusantara of Law and Politic Review, 2026)
The rapid integration of digital technologies into healthcare has fundamentally reshaped the legal framework governing healthcare service delivery. Medical consultations, informed consent, health records, prescriptions, and payment systems are increasingly conducted through electronic platforms, altering the manner in which legal relationships between patients and healthcare providers are established and performed. This transformation raises important legal issues concerning the validity of electronic healthcare contracts, the legal status of therapeutic agreements concluded in digital environments, the protection of personal health data, and the allocation of legal responsibility among healthcare professionals, healthcare institutions, and electronic system providers. This research employs normative legal research using statutory, conceptual, and analytical approaches. Primary legal materials include the Indonesian Civil Code, Law Number 17 of 2023 on Health, Law Number 27 of 2022 on Personal Data Protection, and Law Number 11 of 2008 on Electronic Information and Transactions as last amended by Law Number 1 of 2024. The study demonstrates that the digitalisation of healthcare services does not alter the juridical nature of the therapeutic agreement as the legal basis of the physician–patient relationship. Digitalisation instead transforms the structure of healthcare service contracts by introducing electronic consent, electronic medical records, digital evidence, and multiple contractual actors whose rights and obligations extend beyond the traditional relationship between patients and healthcare professionals. Existing legal provisions have yet to provide a comprehensive framework governing these evolving contractual relationships. A reconstruction of healthcare service contracts is therefore required to accommodate digital healthcare practices while preserving legal certainty, safeguarding patients' rights, ensuring personal data protection, and maintaining accountability within Indonesia's healthcare system.